Verbal overshadowing of face memory does occur in children too! - Dehon, Hedwige; Vanootighem, Valentine; Brédart, Serge (Frontiers in Psychology, 2013)
Verbal descriptions of unfamiliar faces have been found to impair later identification of these faces in adults, a phenomenon known as the “verbal overshadowing effect” (VOE). Although determining whether children are good at describing unfamiliar individuals and whether these descriptions impair their recognition performance is critical to gaining a better understanding children's eyewitness ability, only a couple of studies have examined this dual issue in children and these found no evidence of VOE. However, as there are some methodological criticisms of these studies, we decided to conduct two further experiments in 7–8, 10–11, and 13–14-year-old children and in adults using a more optimal method for the VOE to be observed. Evidence of the VOE on face identification was found in both children and adults. Moreover, neither the accuracy of descriptions, nor delay nor target presence in the lineup was found to be associated with identification accuracy. The theoretical and developmental implications of these findings are discussed.